Heart rate variability and the contribution of parasympathetic reactivation to heart rate recovery following maximal exercise in endurance athletes - Vecchiarelli, E.; Bentley, R. F.; Banks, L.; Thomas, S. G.; Goodman, J. M. (Applied Physiology, Nutrition, and Metabolism, 2018)
Heart rate recovery (HRR) following maximal exercise and heart rate variability (HRV) are non-invasive measures of cardiac autonomic balance and are favourably influenced by increased physical activity. However, in individuals with long-standing history of high-volume exercise performed well-beyond physical activity guidelines, the effect on these measures is less clear. This study evaluated HRV and HRR following maximal exercise in endurance athletes (EA) and recreationally active individuals (REC). Thirty-six EAs (53±5 years) and 19 RECs (56±5 ears) completed graded maximal exercise with heart rate (HR) measured continuously post-exercise for 13-minutes. HRV was measured using time-domain (RMSSD30) analysis during dynamic and stable HRR, and frequency-domain (LF, HF, LF/HF) indices during stable HRR. On average, EAs performed significantly more 10-year vigorous exercise hours than RECs (3497, 2714-4983 hours; 975, 0-2041 hours (p<0.05), respectively). EAs had a lower resting HR (p=0.009), but similar peak HR (p=0.47). HRR was greater in EAs (p<0.004), although not when expressed as a percentage of baseline HR (p=0.2). EAs had greater RMSSD (p<0.01) and HF (p=0.045) following exercise, in addition to LF trending in a similar direction (p=0.052) and LF/HF remaining similar between groups (p=0.7). These results suggest that while intensive endurance training promotes faster HRR by parasympathetic reactivation, accompanied elevations in sympathetic tone provides a similar sympatho-vagal balance although at a greater absolute level.